Design, synthesis, and molecular docking of novel 3, 5‐disubstituted‐1, 3, 4‐oxadiazole derivatives as iNOS inhibitors. Issue 8 (9th May 2021) - Koksal, Meric; Dedeoglu‐Erdogan, Ayca; Bader, Marwa; Gurdal, Enise E.; Sippl, Wolfgang; Reis, Rengin; Ozgurbuz, Melda; Sipahi, Hande; Celik, Turgay
Abstract: To obtain new anti‐inflammatory agents, recent studies have aimed to replace the carboxylate functionality of nonsteroidal anti‐inflammatory drugs with less acidic heterocyclic bioisosteres like 1, 3, 4‐oxadiazole to protect the gastric mucosa from free carboxylate moieties. In view of these observations, we designed and synthesized a series of 3, 5‐disubstituted‐1, 3, 4‐oxadiazole derivatives as inhibitors of prostaglandin E2 (PGE2 ) and NO production with an improved activity profile. As initial screening, and to examine the anti‐inflammatory activities of the compounds, the inhibitions of the productions of lipopolysaccharide‐induced NO and PGE2 in RAW 264.7 macrophages were evaluated. The biological assays showed that, compared with indomethacin, compounds 5a, 5g, and 5h significantly inhibited NO production with 12.61 ± 1.16, 12.61 ± 1.16, and 18.95 ± 3.57 µM, respectively. Consequently, the three compounds were evaluated for their in vivo anti‐inflammatory activities. Compounds 5a, 5g, and 5h showed a potent anti‐inflammatory activity profile almost equivalent to indomethacin at the same dose in the carrageenan‐induced paw edema test. Moreover, the treatment with 40 mg/kg of 5h produced significant anti‐inflammatory activity data. Furthermore, docking studies were performed to reveal possible interactions with the inducible nitric oxide synthase enzyme. Docking results were able to rationalize the biological activity data of the studied inhibitors. In summary, our data suggest that compound 5h is identified as a promising candidate for further anti‐inflammatory drug development with an extended safety profile. Abstract : A series of 3, 5‐disubstituted‐1, 3, 4‐oxadiazoles was designed and synthesized as NO and PGE2 production inhibitors with an improved activity profile. Three compounds were found to have significant inhibitory potential against NO production, compared with the reference drug indomethacin, and were examined for in vivo anti‐inflammatory activity. Their probable interactions with the iNOS enzyme were supported by docking studies.